Tantalum ring and preparation method thereof

By forming a two-layer structure of titanium film and tantalum film on the steel ring, the problem of high preparation cost of tantalum ring is solved, and the low-cost preparation and efficient sputtering performance of tantalum ring is achieved.

CN119121175APending Publication Date: 2024-12-13LEADING THIN FILM MATERIALS (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411044440.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the preparation method of tantalum ring is high in cost and the process is complex, making it difficult to achieve low-cost preparation of tantalum rings.

Method used

By first forming a titanium film on the surface of the steel ring, then forming a tantalum film on the titanium film, forming a two-layer film structure of tantalum ring, titanium tetrafluoride and reducing gas are used for one deposition, and then using tantalum pentafluoride and reducing gas. The secondary deposition of gas reduces the use of pure tantalum.

Benefits of technology

The use of tantalum metal is reduced, the preparation cost is reduced, and the adhesion and sputtering efficiency of the film layer are improved through the combination of titanium film and tantalum film, and the service life of the target material is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004973122390000071
    Figure BDA0004973122390000071
  • Figure BDA0004973122390000081
    Figure BDA0004973122390000081
  • Figure BDA0004973122390000082
    Figure BDA0004973122390000082
Patent Text Reader

Abstract

The invention belongs to the field of metal processing, and discloses a tantalum ring preparation method which comprises the following steps: cleaning and drying a steel ring; then introducing a titanium source and reducing gas into the steel ring in a vacuum environment, heating, and depositing titanium on the surface of the steel ring through chemical vapor deposition to obtain a titanium ring; and finally, introducing a tantalum source and reducing gas into the titanium ring in a vacuum environment, heating, and depositing tantalum on the surface of the titanium ring through chemical vapor deposition to obtain the tantalum ring. According to the scheme, a titanium film and a tantalum film are respectively plated on the steel ring by utilizing a vapor deposition method, and through combination of the titanium film and the tantalum film, the performance of the film is not changed when the using amount of tantalum is reduced, so that the service life of the titanium ring is prolonged. In addition, the invention also discloses the tantalum ring prepared by the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal processing, and in particular to a tantalum ring and a preparation method thereof. Background Art

[0002] At present, sputtering is usually used to form an electrode film on the surface of a semiconductor structure. Sputtering is a coating method of physical vapor deposition (PVD), which is a process in which charged particles bombard a target material, causing surface atomic collisions and energy and momentum transfer in the target material, and the target atoms escape from the surface and are deposited on the substrate. However, since the direction in which the charged particles bombard the target material is uncertain, the target atoms escaping from the target surface have poor directionality, that is, the target atoms will leave the target surface from all angles and then reach the substrate surface in a straight line, which makes the target atoms have poor coverage of the bottom and side walls of the contact holes or through holes on the substrate surface, and the side walls of the steps. Therefore, in order to achieve better coverage of the bottom and side walls of the contact holes or through holes and the side walls of the steps, collimated sputtering is usually used. Collimated sputtering usually places a ring structure in the sputtering equipment to constrain the motion trajectory of the sputtered particles. In other words, the ring structure plays a role in focusing high-energy particles during the sputtering process.

[0003] At the same time, during the sputtering process, high-energy particles continuously bombard the surface of the target material, causing the surface temperature of the target material to rise, which is prone to thermal stress, resulting in the cracking or deformation of the target material. The high melting point and excellent corrosion resistance of the tantalum ring enable it to withstand high temperature and high-energy particle bombardment, effectively protecting the target material from damage. In addition, the high thermal conductivity of the tantalum ring also helps to quickly conduct heat to the surrounding area of ​​the target material, reduce the increase in the surface temperature of the target material, further reduce the risk of damage to the target material, and the tantalum ring can improve the sputtering efficiency. During the sputtering process, the tantalum ring can absorb part of the sputtering material to form tantalum compounds, thereby reducing the loss of sputtering materials and improving sputtering efficiency. In addition, the high surface smoothness and precision of the tantalum ring help to improve the stability and uniformity of the sputtering process and ensure the thickness and composition uniformity of the film. In addition, the tantalum ring also has good chemical stability and corrosion resistance, can maintain stable performance under various sputtering conditions, and is not easily affected by factors such as gas and sputtering materials. This enables the tantalum ring to maintain high performance for a long time during the sputtering process, improve production efficiency, and extend the service life of the target material. The target material is the core material in the sputtering process, and its quality and stability directly affect the quality and performance of the film. The protective effect of the tantalum ring and high-efficiency sputtering can extend the service life of the target material, reduce the number of target replacements, and reduce production costs. In general, the importance of tantalum rings in the sputtering process cannot be ignored. It can not only protect the target material and improve the sputtering efficiency, but also improve the quality and performance of the film, and plays a vital role in the stability and reliability of the sputtering process. Therefore, when carrying out the sputtering process, it is very important to choose the right tantalum ring material and a high-quality tantalum ring manufacturer to ensure the smooth progress of the sputtering process and the improvement of the film quality.

[0004] Tantalum rings are required in tantalum target sputtering. Tantalum is a rare strategic resource and high-purity tantalum is expensive. Therefore, it is necessary to explore a tantalum ring preparation method that reduces the amount of tantalum metal used.

[0005] Among them, Chinese patent application 201910128675.7 discloses a method for preparing a high-purity tantalum sputtering target by chemical vapor deposition. In this scheme, tantalum pentafluoride is used as a raw material, and tantalum is deposited on the surface of the base material by chemical deposition with a reducing gas to form a tantalum film. The one-step method used in this scheme to prepare tantalum targets is conducive to ensuring the quality of tantalum target products and avoiding high production costs caused by secondary processing pollution.

[0006] Chinese patent application 202211316953.X discloses a material preparation method for forming a tantalum / tantalum-iron gradient layer on the surface of carbon steel. The scheme first places the target material in a vacuum chamber, introduces an inert gas, applies voltage and heats up for bombardment pretreatment, and then uses the double glow cross-link discharge phenomenon to alternately change and adjust the voltage and current of the tantalum target material and the carbon steel substrate, so that the temperature gradient of the carbon steel substrate rises to a predetermined temperature for activation; then heats up to a predetermined temperature and allows the tantalum element to diffuse uniformly at a constant temperature on the surface of the substrate; finally, the tantalum target voltage is increased, so that the sputtering rate of the tantalum element is greater than the reverse sputtering rate and a tantalum / tantalum-iron gradient film layer is quickly deposited on the surface of the carbon steel substrate. In this scheme, double glow plasma surface metallurgy technology is used to modify the surface of the metal substrate. Although the obtained base material has good performance, the process is relatively complicated.

[0007] The problem that this proposal needs to solve: How to propose a low-cost method for preparing tantalum rings. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a tantalum ring, which comprises depositing titanium tetrafluoride and reducing gas on the surface of a steel ring to form a titanium film; and then depositing tantalum pentafluoride and reducing gas on the titanium film to form a tantalum film, thereby obtaining a tantalum ring having a two-layer film structure.

[0009] To achieve the above object, the present application discloses a method for preparing a tantalum ring, comprising the following steps:

[0010] Step 1: Clean and dry the steel ring;

[0011] Step 2: Under a vacuum environment, titanium is deposited on the surface of the steel ring obtained in step 1 to obtain a titanium ring;

[0012] Step 3: Under vacuum conditions, tantalum is deposited on the surface of the titanium ring obtained in step 2 to obtain a tantalum ring;

[0013] And in step 2, the thickness of titanium deposited on the surface of the steel ring is 100 to 200 nm;

[0014] In step 3, the thickness of the tantalum deposited on the surface of the titanium ring is 450-550 nm.

[0015] Preferably, the deposition method in step 2 is any one of physical vapor deposition, chemical vapor deposition, low pressure chemical vapor deposition, and plasma enhanced chemical vapor deposition;

[0016] The deposition method in step 3 is any one of physical vapor deposition, chemical vapor deposition, low pressure chemical vapor deposition, and plasma enhanced chemical vapor deposition.

[0017] Preferably, the deposition method of step 2 is chemical vapor deposition, and step 2 specifically comprises: introducing a titanium source and a reducing gas into the steel ring obtained in step 1 under a vacuum environment, heating, and depositing titanium on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring;

[0018] The deposition method of step 3 is chemical vapor deposition. Specifically, step 3 is as follows: a tantalum source and a reducing gas are introduced into the titanium ring obtained in step 2 under a vacuum environment, and the titanium ring is heated. By chemical vapor deposition, tantalum is deposited on the surface of the titanium ring to obtain a tantalum ring.

[0019] Preferably, the cleaning process in step 1 is: subjecting the steel ring to ultrasonic cleaning, acid cleaning, water washing, and ethanol washing in sequence to obtain a cleaned steel ring.

[0020] Preferably, the titanium source in step 2 is at least one of TiCl4, Ti(OMe)4, and Ti(OEt)4.

[0021] Preferably, the tantalum source in step 3 is at least one of TaCl5, TaF5, and TaBr5.

[0022] Preferably, the total thickness of the titanium deposited on the surface of the steel ring and the tantalum deposited on the surface of the titanium ring is 650±50 nm.

[0023] Preferably, the heating temperature in step 2 is 600-700° C.;

[0024] The heating temperature in step 3 is 900-1000°C.

[0025] In addition, the present application also discloses a tantalum ring, which is prepared by the above-mentioned tantalum ring preparation method.

[0026] The beneficial effects of the present invention are:

[0027] The present invention provides a method for preparing a tantalum ring, wherein titanium tetrafluoride and reducing gas are deposited once on the surface of a steel ring to form a titanium film; and tantalum pentafluoride and reducing gas are deposited twice on the basis of the titanium film to form a tantalum film, thereby obtaining a tantalum ring having a two-layer film structure. The combination of titanium film and tantalum film is used to replace the pure tantalum film structure, thereby achieving the purpose of reducing the use of rare metal tantalum, thereby reducing costs and saving resources. DETAILED DESCRIPTION

[0028] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0029] Example 1

[0030] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0031] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TiCl4 and H2 are introduced, and heated to 650°C, and titanium is deposited on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring, and the thickness of the titanium film is 150nm;

[0032] Step 3: The titanium ring prepared in step 2 is placed in a vacuum environment, TaCl5 and H2 are introduced, and heated to 950°C. Tantalum is deposited on the surface of the titanium ring by chemical vapor deposition to obtain a tantalum ring. The thickness of the tantalum film is 500nm.

[0033] Example 2

[0034] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0035] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TiCl4 and H2 are introduced, and heated to 700°C, and titanium is deposited on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring, and the thickness of the titanium film is 200nm;

[0036] Step 3: The titanium ring prepared in step 2 is placed in a vacuum environment, TaCl5 and H2 are introduced, and heated to 900°C. Tantalum is deposited on the surface of the titanium ring by chemical vapor deposition to obtain a tantalum ring. The thickness of the tantalum film is 450nm.

[0037] Example 3

[0038] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0039] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TiCl4 and H2 are introduced, and heated to 600°C, and titanium is deposited on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring, and the thickness of the titanium film is 100 nm;

[0040] Step 3: The titanium ring prepared in step 2 is placed in a vacuum environment, TaCl5 and H2 are introduced, and heated to 1000°C. Tantalum is deposited on the surface of the titanium ring by chemical vapor deposition to obtain a tantalum ring. The thickness of the tantalum film is 550nm.

[0041] Example 4

[0042] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0043] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TiCl4 and H2 are introduced, and heated to 650°C, and titanium is deposited on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring, and the thickness of the titanium film is 250nm;

[0044] Step 3: The titanium ring prepared in step 2 is placed in a vacuum environment, TaCl5 and H2 are introduced, and heated to 950°C. Tantalum is deposited on the surface of the titanium ring by chemical vapor deposition to obtain a tantalum ring. The thickness of the tantalum film is 400 nm.

[0045] Example 5

[0046] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0047] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TiCl4 and H2 are introduced, and heated to 650°C, and titanium is deposited on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring, and the thickness of the titanium film is 50nm;

[0048] Step 3: The titanium ring prepared in step 2 is placed in a vacuum environment, TaCl5 and H2 are introduced, and heated to 950°C. Tantalum is deposited on the surface of the titanium ring by chemical vapor deposition to obtain a tantalum ring. The thickness of the tantalum film is 600nm.

[0049] Example 6

[0050] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0051] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TiCl4 and H2 are introduced, and heated to 650°C, and titanium is deposited on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring, and the thickness of the titanium film is 200nm;

[0052] Step 3: Place the titanium ring obtained in step 2 under vacuum, introduce TaCl5 and H2, heat to 950°C, and deposit tantalum on the surface of the titanium ring by chemical vapor deposition to obtain a tantalum ring with a tantalum film thickness of 50 nm.

[0053] Example 7

[0054] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0055] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TiCl4 and H2 are introduced, and heated to 650°C, and titanium is deposited on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring, and the thickness of the titanium film is 50nm;

[0056] Step 3: Place the titanium ring obtained in step 2 under vacuum, introduce TaCl5 and H2, heat to 950°C, and deposit tantalum on the surface of the titanium ring by chemical vapor deposition to obtain a tantalum ring with a tantalum film thickness of 50 nm.

[0057] Comparative Example 1

[0058] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0059] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TaCl5 and H2 are introduced, and heated to 950°C. Tantalum is deposited on the surface of the steel ring by chemical vapor deposition to obtain a tantalum ring. The thickness of the tantalum film is 650nm.

[0060] Comparative Example 2

[0061] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0062] Step 2: The steel ring prepared in step 1 is placed in a vacuum environment, TiCl4 and H2 are introduced, and heated to 650°C, and titanium is deposited on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring, and the thickness of the titanium film is 650nm;

[0063] Comparative Example 3

[0064] Step 1: First, ultrasonically clean the steel ring for 3 minutes, then acid wash for 3 minutes, then wash with pure water for 3 minutes, and finally wash with anhydrous alcohol for 3 minutes, and blow dry with clean nitrogen;

[0065] Step 2: Place the steel ring in step 1 under vacuum, introduce hafnium tetrachloride and H2, heat to 650°C, and deposit hafnium on the surface of the steel ring by chemical vapor deposition to obtain a hafnium ring, wherein the thickness of the hafnium film is 150 nm;

[0066] Step 3: Place the titanium ring obtained in step 2 in a vacuum environment, introduce TaCl5 and H2, heat to 950°C, and deposit tantalum on the surface of the titanium ring by chemical vapor deposition to obtain a tantalum ring with a tantalum film thickness of 500nm.

[0067] Comparative Example 4

[0068] A pure tantalum ring having the same size as that in Example 1 was used as a comparative example. It should be noted that the pure tantalum ring refers to a pure tantalum ring consisting only of tantalum metal.

[0069] Performance Testing

[0070] Film adhesion: Use 3M tape to adhere to 100 grid areas, the number of unpeeled areas / 100. The higher the number of unpeeled areas, the stronger the film adhesion.

[0071] The performance test results of the tantalum rings in Examples 1-7 and Comparative Examples 1-4 are shown in Table 1:

[0072] Table 1

[0073]

[0074]

[0075] Results Analysis

[0076] 1. It can be seen from Examples 1-4 and Comparative Example 1 that in the tantalum ring of Example 1, the thickness of the titanium film is 150 nm, and the thickness of the tantalum film is 500 nm;

[0077] In Example 2, the thickness of the titanium film in the tantalum ring is 200 nm, and the thickness of the tantalum film is 450 nm;

[0078] In Example 3, the thickness of the titanium film in the tantalum ring is 100 nm, and the thickness of the tantalum film is 550 nm;

[0079] Example 4 The thickness of the titanium film in the tantalum ring is 250 nm, and the thickness of the tantalum film is 400 nm. The experimental data are shown in Table 2:

[0080] Table 2

[0081]

[0082] It can be seen from the experimental data that when the thickness of the titanium film in the tantalum ring increases from 100nm to 200nm, the adhesion between the titanium film and the steel ring is constantly increasing. However, when the thickness of the titanium film increases from 200nm to 250nm, although the adhesion of the film layer is also enhanced to a certain extent, the amplitude is very small.

[0083] When the thickness of the tantalum film in the tantalum ring increases from 400nm to 550nm, the reflectivity of the sputtered particles during the entire life cycle of the tantalum ring continues to decrease, indicating that the thickness of the tantalum film is conducive to improving the reflectivity of the sputtered particles during the entire life cycle of the tantalum ring. However, due to the high cost of tantalum metal, the material cost is gradually increasing with the increase in the thickness of the tantalum film.

[0084] 2. It can be seen from Examples 5-7 that the thickness of the titanium film in the tantalum ring of Example 5 is 50 nm, and the thickness of the tantalum film is 600 nm;

[0085] In Example 6, the thickness of the titanium film in the tantalum ring is 200 nm, and the thickness of the tantalum film is 50 nm;

[0086] Example 7 The thickness of the titanium film in the tantalum ring is 50 nm, and the thickness of the tantalum film is 50 nm. The experimental data of the above tantalum ring are shown in Table 3:

[0087] Table 3

[0088]

[0089] It can be seen from the experimental data that when the thickness of the titanium film is less than 100nm, the film adhesion between the titanium film and the steel ring decreases significantly, and when the thickness of the titanium film is only 50nm, the film adhesion is only 66%.

[0090] Furthermore, when the thickness of the tantalum film in the tantalum ring is too thin, the reflectivity of the sputtered particles during the entire life cycle of the tantalum ring will also be too thin and will easily fall off during the sputtering process, resulting in a particularly large de-reflectivity.

[0091] 3. It can be seen from Example 1 and Comparative Examples 1-2 that the film layer of the steel ring in Example 1 is composed of a titanium film and a tantalum film;

[0092] In Comparative Example 1, the film layer of the steel ring is composed of a tantalum film;

[0093] In Comparative Example 2, the film layer of the steel ring is composed of a titanium film. The experimental data of the tantalum ring or titanium ring prepared above are shown in Table 4:

[0094] Table 4

[0095]

[0096] It can be seen from the experimental data that when the film layer of the tantalum ring is entirely formed by tantalum film, according to the rule that the thicker the tantalum film is, the higher the reflectivity of the sputtered particles during the entire life cycle, its reflectivity should be less than 1%. However, the reflectivity of the sputtered particles during the entire life cycle of Comparative Example 1 is greater than 30%. The reason is that without the film layer adhesion provided by the titanium film, the adhesion of the tantalum film on the tantalum ring is extremely poor and it is easy to fall off during use, so its reflectivity is greater than 30%.

[0097] When the film layer of the tantalum ring is entirely formed by a titanium film, the film layer has excellent adhesion, but the titanium film cannot provide the sputtering performance of the tantalum film like the tantalum film, so the sputtering particle reflectivity over the entire life cycle is greater than 60%.

[0098] It can be seen from Example 1 and Comparative Example 1 that the cost of the tantalum ring made by combining the titanium film and the tantalum film is reduced by 740 yuan per piece compared with the cost of the tantalum ring made by a single tantalum film.

[0099] 4. It can be seen from Example 1 and Comparative Example 3 that in Comparative Example 3, hafnium, a homologous element of titanium, is used to replace titanium to form a hafnium film and form a double-layer coating with a tantalum film to obtain a tantalum ring, but the adhesion of the film layer is only 54%, which is much less than the adhesion provided by the titanium film.

[0100] Furthermore, since the hafnium film has less adhesion, it cannot firmly adsorb the tantalum film like the titanium film, which causes the tantalum film to fall off more easily during use, further resulting in a sputtered particle reflectivity of >20% over its entire life cycle.

[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a tantalum ring, It is characterized in that The steps include: Step 1: Clean and dry the steel ring; Step 2: Under a vacuum environment, titanium is deposited on the surface of the steel ring obtained in step 1 to obtain a titanium ring; Step 3: Under a vacuum environment, tantalum is deposited on the surface of the titanium ring obtained in step 2 to obtain a tantalum ring; And in step 2, the thickness of titanium deposited on the surface of the steel ring is 100 to 200 nm; In step 3, the thickness of the tantalum deposited on the surface of the titanium ring is 450-550 nm.

2. The method for preparing a tantalum ring according to claim 1, It is characterized in that The deposition method in step 2 is any one of physical vapor deposition, chemical vapor deposition, low pressure chemical vapor deposition, and plasma enhanced chemical vapor deposition; The deposition method in step 3 is any one of physical vapor deposition, chemical vapor deposition, low pressure chemical vapor deposition, and plasma enhanced chemical vapor deposition.

3. The method for preparing a tantalum ring according to claim 1, It is characterized in that The deposition method of step 2 is chemical vapor deposition, and step 2 specifically comprises: introducing a titanium source and a reducing gas into the steel ring obtained in step 1 under a vacuum environment, heating, and depositing titanium on the surface of the steel ring by chemical vapor deposition to obtain a titanium ring; The deposition method of step 3 is chemical vapor deposition, and step 3 specifically includes: introducing a tantalum source and a reducing gas into the titanium ring obtained in step 2 under a vacuum environment, heating, and depositing tantalum on the surface of the titanium ring through chemical vapor deposition to obtain a tantalum ring.

4. The method for preparing a tantalum ring according to claim 1, It is characterized in that The cleaning process in step 1 is: subjecting the steel ring to ultrasonic cleaning, acid cleaning, water cleaning, and ethanol cleaning in sequence to obtain a cleaned steel ring.

5. The method for preparing a tantalum ring according to claim 1, It is characterized in that The titanium source in step 2 is TiCl 4 、Ti(OMe) 4 、Ti(OEt) 4 At least one of .

6. The method for preparing a tantalum ring according to claim 1, It is characterized in that The tantalum source in step 3 is TaCl 5 、TaF 5 、TaBr 5 At least one of .

7. The method for preparing a tantalum ring according to claim 1, It is characterized in that The total thickness of the titanium deposited on the surface of the steel ring and the tantalum deposited on the surface of the titanium ring is 650±50 nm.

8. The method for preparing a tantalum ring according to claim 1, It is characterized in that The heating temperature in step 2 is 600-700° C.; The heating temperature in step 3 is 900-1000°C.

9. A tantalum ring made by the method for making a tantalum ring according to any one of claims 1 to 8.